A Systems-Based Approach to Safeguard the Strawberry Industry from Virus Diseases. (30th November 2016) - Tzanetakis, Ioannis E.
ABSTRACT: Strawberry is susceptible to several systemic pathogens and, in particular, viruses. There are several examples of disease epidemics that resulted from virus-infected propagation material and led to losses estimated in the tens of millions of dollars. This communication focuses on actions needed to minimize the risk of similar outbreaks by developing a systems-based approach from breeding to the commercial field. This includes the development of molecular biology and bioinformatic tools that allow for the detection of all known viruses infecting strawberry but most importantly for the discovery of viruses that circulate in the system undetected and may have contributed to past epidemics. Surveys in commercial fields have yielded a map of the most prevalent viruses in strawberry production areas across the United States, knowledge that will be used in the nascent National Certification Program for Strawberry.